Vapor-Liquid Equilibria for Carbon Dioxide + 3,3,3-Trifluoropropene Binary Mixtures at Temperatures between (288 and 348) K - Sadaghiani, M.S.; Arami-Niya, Arash; Marsh, B.; Al Ghafri, S.Z.S.; May, E.F. (2021)
Accurate property data for mixtures of hydrofluoroolefins with refrigerants like CO2 are needed by industry to design safe and efficient refrigeration systems that employ low global warming potential working fluids. However, data available for these mixtures, particularly at conditions of vapor-liquid-equilibrium (VLE), are limited. In this work, the VLE of CO2 and HFO-1243zf binary mixtures was measured along five isotherms at temperatures between (288 and 348) K and pressures between (0.68 and 7.69) MPa. The new VLE data are compared with the predictions of a Helmholtz free energy model that utilizes GERG-2008 mixing rules. Adjusting the model's binary interaction parameters (BIPs) to force agreement with the new measurements reduced the root-mean-square deviation (RMSD) of the data from the model by 45% relative to the default BIPs. Additionally, the data were compared with predictions from the Peng-Robinson advanced equation of state (PRA-EOS) with a one-fluid mixing rule and a fixed binary interaction parameter which was subsequently tuned to the experimental data. The tuned PRA-EOS could represent the experimental CO2 mole fractions with an RMSD of 0.012, which is more than 2 times larger than the average experimental uncertainty, while the RMSD of the tuned Helmholtz free energy model from the experimental data was 0.009. The accurate data and improved model presented in this work will aid the development of environmentally friendly refrigerant mixtures.